2008
DOI: 10.1508/cytologia.73.349
|View full text |Cite
|
Sign up to set email alerts
|

The Homology and Relationship of Human (Homo sapiens) Chromosomes 1, 19 and Dusky Langur (Trachypithacus obscurus) Chromosomes 6, 8 Demonstrated with Chromosome Painting

Abstract: SummaryChromosomal relationship between humans and dusky langurs (Trachypithecus obscurus, 2nϭ44) was established by chromosome painting using chromosome specific DNA probes of the human chromosome 1 and 19 which each gave hybridization signals on two non-homologous dusky langur chromosomes. The results show that the human chromosome 1 and 19 probes hybridized to three regions of dusky langur on the autosomes 6 and 8. The human chromosome 1 probe hybridized to one region on the dusky langur chromosome 6 and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(11 reference statements)
2
5
1
Order By: Relevance
“…Our study is in contrast to Sangpakdee et al (2008) and Tanomtong et al (2012), which found heteromorphic NOR of dusky langur (T. obscurus) on pair 19 and 17, respectively. In addition, Nie et al (1998) found heteromorphic NOR of Phayre s langur (T. phayrei) and Francois langur (T. francoisi) on pair 21.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Our study is in contrast to Sangpakdee et al (2008) and Tanomtong et al (2012), which found heteromorphic NOR of dusky langur (T. obscurus) on pair 19 and 17, respectively. In addition, Nie et al (1998) found heteromorphic NOR of Phayre s langur (T. phayrei) and Francois langur (T. francoisi) on pair 21.…”
Section: Resultscontrasting
confidence: 99%
“…This result compares with other langurs in Thailand as P. phayrei has metacentic, submetacentric, and acrocentric autosomes equal to 22-16-4 and 22-18-2 as reported by Chen et al (1981) and Nie et al (1998), respectively. The other langur species in Thailand, P. obscurus, has metacentic, submetacentric, and acrocentric autosomes equal to 26-12-2, 28-12-2, 22-18-2 and 12-16-4 as reported by Chiarelli (1963), Ponsa et al (1983), Sangpakdee et al (2008) and Tanomtong et al (2012), respectively. In addition, the comparative of other langur cytogenetic data on this study and previous studies are shown in Table 2.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…This result agrees with the chromosome characteristics of others in the subfamily Colobinae in Thailand. T. cristatus (Hsu and Benirschke 1970, Ponsà et al 1983, Bigoni et al 1997a, T. phayrei (Nie et al 1998), and T. obscures (Chiarelli 1963, Hsu and Benirschke 1971, Sangpakdee et al 2008 all have the same chromosome number of 2n = 44 and most have NF = 88. In previous studies, the diploid number of both African (genus Colobus) and Asian (genus Presbytis) colobines was found to be 2n = 44 and most have NF = 88 (Chiarelli 1963, Ushima et al 1964.…”
Section: Discussionmentioning
confidence: 99%